PEMANTAUAN OUTPUT GENSET SECARA REAL TIME DENGAN MIKROKONTROLER DAN APLIKASI TELEGRAM - Putri Adhitya Pradhanny Phuspitasari; Teguh Arifianto; Andri Pradipta; Sunaryo Sunaryo (Jurnal Kajian Teknik Elektro, 2025)
Manual monitoring of generator sets remains a challenge for some companies due to inefficiencies in labor and time usage. Delays in detecting the operational status of generator sets can lead to disruptions in power supply, particularly in industrial and essential service sectors. To address this issue, this study develops a microcontroller based generator output monitoring system prototype integrated with the telegram application to provide real time notifications. The proposed method includes hardware design with a current sensor installed on the generator output cable and microcontroller programming to measure voltage, current, and frequency parameters. The measured data is then compared with a multimeter to ensure system accuracy. Testing results indicate that the system effectively displays generator output information on an LCD screen and sends automatic notifications via telegram when the generator is active. If the generator is not operating, the system does not send notifications, thereby reducing unnecessary communication. The main advantage of this system lies in its IoT integration, which enables remote generator monitoring efficiently, delivers real time information to users, and minimizes reliance on manual inspections. This system is designed to enhance the efficiency of generator monitoring and has the potential for implementation across various industrial sectors.